Superfine cement-based composite grouting material and preparation method thereof

CN123003203APending Publication Date: 2026-10-30NORTHWEST RES INST CO LTD OF C R E C +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611447319.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-17
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]解决的技术问题:现有水泥基注浆材料在西北干旱地区深细裂缝修复中,可灌性与抗裂性难以兼顾,高水灰比下强度低、收缩大,且缺乏多组分协同优化,无法适应干旱低湿环境施工需求

Benefits of technology

[0018]本方案通过超细水泥、硅灰与纳米二氧化硅构建“微米-亚微米-纳米”连续梯度颗粒填充体系,实现紧密堆积以降低孔隙率,同时利用硅灰与纳米二氧化硅的高火山灰活性持续生成C-S-H凝胶,显著提升了硬化体的致密性与力学强度;通过SAP树脂的预吸水裹壳工艺形成人工矿物壳层,既延缓了SAP的过度吸水以避免浆体增稠,又在其释水后借助壳层崩解释放的活性矿物颗粒填充空腔缺陷,从而在实现智能内养护抑制干缩开裂的同时,有效消除了传统SAP对强度的负面影响;配合膨胀剂的化学收缩补偿、缓凝剂对可操作时间的精准调控以及消泡剂对有害气泡的消除,使材料在马氏漏斗流动度仅27~38s的低黏度状态下,依然能够实现0.05mm级微裂缝的低压可灌性,并将28d收缩率大幅降低至0.048%~0.071%,28d抗压强度提升32%~58%至50.7~60.8MPa,可操作时间延长至68~118min,综合实现了高流动性、长操作窗口、高早后期强度与极低收缩率的协同统一,特别适用于西北干旱风沙地区混凝土深细裂缝的修复工程。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123003203A_ABST
    Figure CN123003203A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of building materials, in particular to a superfine cement-based composite grouting material and a preparation method thereof, which comprises the following components based on the mass of superfine cement: 6-12% of silica fume, 0.5-1.5% of silicon dioxide powder, 0.3-0.8% of a retarder, 0.5-0.6 of a water-cement ratio, 0.2-0.5% of SAP resin, 0.1-0.3% of a defoaming agent and 7-10% of an expansive agent; in the scheme, the superfine cement, the silica fume and the nano-silicon dioxide are used to build a micron-submicron-nano continuous gradient filling system to realize close packing, the artificial mineral shell coating technology of the SAP resin is used to realize the dual synergy of intelligent internal curing and cavity defect compensation, the chemical shrinkage compensation of the expansive agent and the accurate regulation of the setting time of the retarder are combined, the synergy of excellent fluidity, high stone strength and extremely low shrinkage rate under a low water-cement ratio is realized, and the technical problems of poor groutability, serious shrinkage and cracking and lack of collaborative optimization of multiple components of the existing materials in the northwest arid environment are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of building materials technology, and in particular to an ultrafine cement-based composite grouting material and its preparation method. Background Technology

[0002] Cracks in concrete structures are among the most common defects in civil engineering. Particularly in the arid and cold northwest, the development of early-stage cracks in concrete is more severe due to the dry climate, large diurnal temperature variations, and severe wind and sand erosion. The strong evaporation and low humidity characteristic of the arid northwest cause rapid loss of moisture from the concrete, exacerbating plastic shrinkage and drying shrinkage. The resulting cracks are often deep and fine – typically 0.05–0.3 mm wide, but reaching depths of tens of millimeters or even deeper. These deep and fine cracks not only affect the structural appearance but, more seriously, provide entry channels for corrosive media (such as sulfates and chlorides in saline soil environments), accelerating steel corrosion and deteriorating concrete durability.

[0003] Currently, materials for repairing concrete cracks are mainly divided into two categories: organic (such as epoxy resin and polyurethane) and inorganic (such as cement-based grouting materials). While organic grouting materials have good fluidity and high bonding strength, their thermal expansion coefficients differ significantly from those of the concrete matrix, making them prone to interfacial debonding in the harsh environment of Northwest China with its large diurnal temperature variations. They also suffer from insufficient aging resistance and high cost. Inorganic cement-based grouting materials, although compatible with concrete and possessing excellent durability, still have limitations such as insufficient injectability (ordinary cement particles are difficult to inject into micro-cracks <0.3mm), high water-cement ratio leading to decreased strength and increased shrinkage, rapid moisture loss in the arid environment of Northwest China causing incomplete hydration and drying shrinkage cracking, and a lack of synergistic optimization design among multiple components resulting in overall performance that fails to meet engineering requirements.

[0004] Therefore, this invention proposes an ultrafine cement-based composite grouting material and its preparation method. By constructing a continuous gradient particle filling system of "micron-submicron-nano" through ultrafine cement, silica fume and nano silica, and combining the artificial mineral shell coating technology of SAP resin with the chemical shrinkage compensation of the expansion agent, the material achieves a synergistic unity of excellent fluidity and high aggregate strength under low water-cement ratio. It effectively inhibits plastic shrinkage and drying shrinkage cracking under arid conditions and significantly improves the material's adaptability to grouting repair of deep and fine cracks in concrete in the windy and sandy areas of Northwest China. Summary of the Invention

[0005] Technical problems to be solved: Existing cement-based grouting materials have difficulty in achieving both groutability and crack resistance in the repair of deep and fine cracks in arid areas of Northwest China. They also have low strength and large shrinkage under high water-cement ratios, and lack multi-component synergistic optimization, making them unsuitable for construction needs in arid and low-humidity environments.

[0006] To address the shortcomings of existing technologies, this invention provides an ultrafine cement-based composite grouting material and its preparation method, thereby solving the technical problems mentioned in the background art.

[0007] To achieve the above objectives, the present invention provides the following technical solution:

[0008] A method for preparing an ultrafine cement-based composite grouting material includes the following steps:

[0009] Step S1: Prepare raw materials according to the following mass ratio: based on the mass of ultrafine cement, silica fume 6%~12%, silica powder 0.5%~1.5%, retarder 0.3%~0.8%, mixing water with a water-cement ratio of 0.5~0.6, SAP resin 0.2%~0.5%, defoamer 0.1%~0.3%, and expanding agent 7%~10%;

[0010] Step S2: Mix the ultrafine cement, silica fume, nano silica powder, retarder, expanding agent and defoamer dry powder to obtain a basic dry powder mixture, and take out 5% of the dry powder mixture by mass of the basic dry powder for separate use.

[0011] Step S3: Take a portion of the mixing water to pre-wet and disperse the SAP resin, add the prepared portion of the basic dry powder mixture for coating treatment, and obtain humidity-responsive water-retaining microparticles.

[0012] Step S4: Mix the remaining dry powder mixture from step S2 with the remaining mixing water, then add the humidity-responsive water-retaining microparticles obtained in step S3, and continue stirring to obtain the grouting slurry.

[0013] In one possible implementation, the specific operation of the pre-wet dispersion in step S3 is as follows: slowly sprinkle the SAP resin into the mixing water, which accounts for 5 times its mass, while stirring, and let it stand for 5 to 8 minutes to form a suspension of hydrogel particles.

[0014] In one possible implementation, the specific operation of the coating process in step S3 is as follows: 5% of the total mass of the base dry powder mixture is sprinkled into the suspension of hydrogel particles, and stirred until the dry powder is evenly coated on the surface of the SAP gel particles to form an artificial mineral shell.

[0015] In one possible implementation, step S4 specifically involves: adding the remaining dry powder mixture and the remaining mixing water into a mixer and stirring at 100 r / min for 2 min, then adding the humidity-responsive water-retaining microparticles and increasing the speed to 400 r / min and stirring for 5 min.

[0016] In one possible implementation, an ultrafine cement-based composite grouting material is prepared by any of the preparation methods described above.

[0017] Beneficial effects compared to existing technologies:

[0018] This solution constructs a continuous gradient particle filling system of "micron-submicron-nano" using ultrafine cement, silica fume, and nano-silica to achieve close packing and reduce porosity. Simultaneously, the high pozzolanic activity of silica fume and nano-silica continuously generates CSH gel, significantly improving the density and mechanical strength of the hardened body. An artificial mineral shell is formed through a pre-water-absorbing coating process of SAP resin. This not only delays excessive water absorption by SAP to prevent slurry thickening but also, upon water release, allows the active mineral particles released by the shell disintegration to fill cavities and defects. This achieves intelligent internal curing to inhibit drying shrinkage and cracking while effectively eliminating the negative impact of traditional SAP on strength. Combined with an expansion agent... The chemical shrinkage compensation, the precise control of the working time by the retarder, and the elimination of harmful bubbles by the defoamer enable the material to achieve low-pressure injection capability for microcracks of 0.05mm level even at a low viscosity state with a Marsh funnel flow rate of only 27~38s. It also significantly reduces the 28-day shrinkage rate to 0.048%~0.071%, increases the 28-day compressive strength by 32%~58% to 50.7~60.8MPa, and extends the working time to 68~118min. It comprehensively achieves a synergistic unity of high fluidity, long working window, high early and late strength, and extremely low shrinkage rate, making it particularly suitable for the repair of deep and fine cracks in concrete in arid and windy areas of Northwest China. Attached Figure Description

[0019] The above description is merely an overview of the technical solution of the present invention. In order to better understand the technical means of the present invention and to implement it in accordance with the contents of the specification, the preferred embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0020] Figure 1 This is a flowchart illustrating the steps involved in preparing an ultrafine cement-based composite grouting material. Detailed Implementation

[0021] Preferred embodiments of the present invention will be described in detail with reference to the accompanying drawings. However, the present invention can also be implemented in various different forms, and therefore the present invention is not limited to the embodiments described below.

[0022] The technical solution in this application embodiment is to solve the problems mentioned in the background art, and the overall idea is as follows:

[0023] This invention provides an ultrafine cement-based composite grouting material, composed of the following components in proportion:

[0024] Based on the quality of ultrafine cement, the following components are used: silica fume 6%~12%, silica powder 0.5%~1.5%, retarder 0.3%~0.8%, water-cement ratio 0.5~0.6, SAP resin 0.2%~0.5%, defoamer 0.1%~0.3%, and expanding agent 7%~10%;

[0025] The functions and synergistic mechanisms of each component are as follows:

[0026] Ultrafine cement: As a basic cementitious material, 1000 to 1200 mesh ultrafine cement is used, with a D90 of no more than 20 micrometers. The ultrafine cement particles are small enough to be injected into micro-cracks, and at the same time, as the first-level micron-scale skeleton particles in the gradient particle filling system, it provides a basic framework for the subsequent stepwise filling of silica fume and nano-silica.

[0027] Silica fume: The silica fume content is 6%~12% of the mass of ultrafine cement, preferably 9%. Its core functions are twofold: First, the average particle size of silica fume particles is 0.1 to 1 micrometer, which can fill the micrometer-level pores between ultrafine cement particles, forming the second stage of the gradient particle filling system; second, silica fume has high pozzolanic activity, reacting secondaryly with calcium hydroxide produced during cement hydration to generate CSH gel, improving the strength of the cementitious mass. Silica fume also improves the fluidity of the slurry and reduces losses over time.

[0028] Silica powder: The amount of nano-silica is 0.5%~1.5% of the mass of ultrafine cement, preferably 1.0%; its core functions are threefold: First, as the finest stage of the gradient particle filling system, it fills the nanoscale pores remaining after the ultrafine cement and silica fume are piled up, realizing continuous and compact packing of "micron-submicron-nano"; Second, as a seed crystal, it accelerates the early hydration of cement and significantly improves early strength; Third, its high pozzolanic activity further consumes calcium hydroxide to generate CSH gel, making the hardened body structure extremely dense.

[0029] Retarder: The dosage of retarder is 0.3% to 0.8% of the mass of ultrafine cement, preferably 0.5%. Due to the high ambient temperature and rapid evaporation of water in the arid Northwest region, the hydration rate of ultrafine cement is relatively fast, which can easily lead to premature setting of the grout and failure to complete the grouting construction. The role of retarder is to extend the workable time of the grout and ensure the smooth progress of the grouting construction. By regulating the hydration rate, it helps to improve the fluidity and stability of the grout. Sodium gluconate, citric acid or boric acid and other commonly used cement retarders in this field are selected as retarders.

[0030] Water-cement ratio: The water-cement ratio is controlled at 0.5~0.6. It should be noted that some of the mixing water is absorbed and stored by the SAP resin during the mixing process, and the amount of free water actually participating in cement hydration is dynamically reduced. The SAP gradually releases water in the subsequent process, achieving the special effect of low free water mixing and high internal curing water supply, thus avoiding the strength loss caused by the traditional high water-cement ratio.

[0031] SAP resin (superabsorbent polymer): The SAP resin dosage is 0.2%~0.5% of the mass of ultrafine cement, preferably 0.3%; it achieves dual-function synergy through artificial mineral shell coating technology.

[0032] Firstly, the intelligent internal curing function: During the mixing stage, SAP resin rapidly absorbs and stores a large amount of free water, forming water-containing gel particles (i.e., "reservoirs") that are uniformly dispersed inside the slurry. When cement hydration consumes free water and the arid environment in Northwest China causes the relative humidity inside the slurry to continuously decrease, SAP resin, relying on its inherent humidity response characteristics, actively releases the stored water gradually along the humidity gradient through gel network contraction, continuously supplying cement hydration and compensating for water loss due to evaporation. This intelligent behavior of "releasing water when drought occurs" fundamentally inhibits plastic shrinkage and drying cracking caused by water loss due to drought.

[0033] Secondly, the structure and function of the artificial mineral shell: In the preparation process, the SAP resin is first pre-absorbed with 5 times the amount of water to a semi-saturated state, and then a dry powder mixture (composed of ultrafine cement, silica fume, nano silica, expansion agent, etc.) accounting for 5% of the total mass of the base dry powder is added to it, so that the dry powder is evenly coated on the surface of the SAP gel particles to form an artificial mineral shell. The shell layer has three key functions: ① Delaying excessive water absorption: The physical barrier of the shell layer slows down the excessive absorption of free water by SAP during subsequent stirring, preventing the slurry from thickening rapidly due to excessive SAP expansion and ensuring good slurry fluidity; ② Defect compensation and interface strengthening: As hydration proceeds, when SAP releases water and shrinks, the outer dry powder shell layer simultaneously disintegrates and releases active mineral particles. These particles directly participate in the hydration reaction to generate CSH gel and ettringite, effectively filling the cavity defects left after SAP releases water, and significantly reducing the negative impact of internal curing on strength; ③ Particle size homogenization and improved injectability: The coated SAP particles have a particle size distribution concentrated in the range of 100~200μm and a regular morphology, facilitating subsequent filtration through a ≥80 mesh sieve and injection into microcracks at low pressure of 0.1~0.6MPa, preventing uncoated SAP from clogging the sieve due to excessive expansion during filtration.

[0034] Expansive agent: The dosage of the expansive agent is 7% to 10% of the mass of ultrafine cement, preferably 8%, and calcium sulfoaluminate, calcium oxide or composite expansive agents can be selected; it generates expansive products such as ettringite through hydration, resulting in moderate volume expansion, which compensates for chemical shrinkage and drying shrinkage during the hardening process of cement stone; the active components released by the disintegration of artificial shell and the hydration products of the expansive agent together fill the water release cavity of SAP, so that the shrinkage compensation extends from the macroscopic volume to the microscopic pore structure, further improving the crack resistance effect.

[0035] Defoamer: The dosage of defoamer is 0.1% to 0.3% of the mass of ultrafine cement, preferably 0.2%; its function is to eliminate harmful air bubbles in the slurry and improve the density and strength of the aggregate.

[0036] Example 1:

[0037] like Figure 1 As shown, this embodiment provides a method for preparing an ultrafine cement-based composite grouting material based on the above-mentioned ultrafine cement-based composite grouting material. The method includes the following steps:

[0038] Step S1, Raw material preparation:

[0039] 1000g ultrafine cement, 90g silica fume (9%), 10g nano silica powder (1.0%), 5.5g sodium gluconate retarder (0.55%), 550g mixing water (water-cement ratio 0.55), 3.5g SAP resin (0.35%), 2.0g polyether defoamer (0.2%), and 85g calcium sulfoaluminate expanding agent (8.5%).

[0040] Step S2, Mixing dry powder:

[0041] The weighed ultrafine silicate cement, silica fume, nano silica powder, retarder, expanding agent and defoamer from step S1 are sequentially added into a forced mortar mixer and stirred at 300 r / min for 8 min to obtain a uniform dry powder mixture.

[0042] In addition, take out 5% of the total mass of the base dry powder mixture and set it aside separately.

[0043] Step S3: Preparation of humidity-responsive water-retaining microparticles:

[0044] Weigh out 5 times the amount of water (by weight of the SAP resin) in a separate container. Slowly sprinkle the SAP resin into the water while stirring rapidly with a glass rod to prevent the SAP resin particles from sticking together and forming gel clumps due to excessive water absorption. Let stand for 5 to 8 minutes to allow the SAP resin to fully absorb the water and form a uniformly dispersed suspension of water-containing gel particles.

[0045] Immediately sprinkle the 5% dry powder mixture reserved in step S1 into the semi-wet SAP gel in batches, while quickly stirring to make the dry powder evenly coat the outer surface of the SAP gel particles and form an artificial mineral shell.

[0046] The above operation, on the one hand, allows the SAP resin to reach a saturated water absorption state in advance by absorbing water in advance, avoiding the rapid thickening of the local slurry due to concentrated water absorption during subsequent stirring; on the other hand, the artificial mineral shell on its outside can slowly disintegrate and participate in hydration when the SAP shrinks and releases water in the later stage, reducing the cavity defects left by the SAP; the shell makes the SAP particle size distribution more uniform (about 100~200μm), which is convenient for subsequent filtration and low-pressure injection.

[0047] Step S4: Mixing and stirring to make pulp:

[0048] Add the remaining dry powder mixture and the remaining mixing water from step S2 to the mixer, start the mixer and stir at 100 r / min for 2 minutes to initially wet and mix the dry powder with the water; then pour the humidity-responsive water-retaining microparticles from step S3 evenly into the mixer, increase the mixer speed to 400 r / min and stir for 5 minutes to obtain the final product.

[0049] Example 2:

[0050] This embodiment provides another method for preparing ultrafine cement-based composite grouting material based on Embodiment 1. The difference between this embodiment and Embodiment 1 is that the dosage of raw materials is reduced. The specific steps are as follows:

[0051] Step S1, Raw material preparation:

[0052] 1000g ultrafine cement, 90g silica fume (6%), 5g nano silica powder (0.5%), 3g citric acid retarder (0.3%), 500g mixing water (water-cement ratio 0.50), 2g SAP resin (0.2%), 1g organosilicon defoamer (0.1%), and 70g calcium oxide expansion agent (7%).

[0053] Step S2, Mixing dry powder:

[0054] The weighed ultrafine silicate cement, silica fume, nano silica powder, retarder, expanding agent and defoamer from step S1 are sequentially added into a forced mortar mixer and stirred at 200 r / min for 10 min to obtain a uniform dry powder mixture.

[0055] In addition, take out 5% of the total mass of the base dry powder mixture and set it aside separately.

[0056] Step S3: Preparation of humidity-responsive water-retaining microparticles:

[0057] Weigh out 5 times the amount of water (by weight of the SAP resin) in a separate container. Slowly sprinkle the SAP resin into the water while stirring rapidly with a glass rod to prevent the SAP resin particles from sticking together and forming gel clumps due to excessive water absorption. Let stand for 5 to 8 minutes to allow the SAP resin to fully absorb the water and form a uniformly dispersed suspension of water-containing gel particles.

[0058] Immediately sprinkle the 5% dry powder mixture reserved in step S1 into the semi-wet SAP gel in batches, stirring rapidly while sprinkling, so that the dry powder is evenly coated on the outer surface of the SAP gel particles, forming an artificial mineral shell.

[0059] Step S4: Mixing and stirring to make pulp:

[0060] Add the remaining dry powder mixture and the remaining mixing water from step S2 to the mixer, start the mixer and stir at 100 r / min for 2 minutes to initially wet and mix the dry powder with the water; then pour the humidity-responsive water-retaining microparticles obtained in step S3 evenly into the mixer, increase the mixer speed to 400 r / min and stir for 5 minutes to obtain the final product.

[0061] Example 3:

[0062] This embodiment provides another method for preparing ultrafine cement-based composite grouting material based on Embodiments 1 and 2. The difference between this embodiment and Embodiments 1 and 2 is that the dosage of raw materials is increased. The specific steps are as follows:

[0063] Step S1, Raw material preparation:

[0064] 1000g ultrafine cement, 120g silica fume (12%), 15g nano silica powder (1.5%), 8g boric acid retarder (0.8%), 600g mixing water (water-cement ratio 0.60), 5g SAP resin (0.5%), 3g polyether defoamer (0.3%), and 100g composite expansion agent (10%).

[0065] Step S2, Mixing dry powder:

[0066] The weighed ultrafine silicate cement, silica fume, nano silica powder, retarder, expanding agent and defoamer from step S1 are sequentially added into a forced mortar mixer and stirred at 200 r / min for 10 min to obtain a uniform dry powder mixture.

[0067] In addition, take out 5% of the total mass of the base dry powder mixture and set it aside separately.

[0068] Step S3: Preparation of humidity-responsive water-retaining microparticles:

[0069] Weigh out 5 times the amount of water (by weight of the SAP resin) in a separate container. Slowly sprinkle the SAP resin into the water while stirring rapidly with a glass rod to prevent the SAP resin particles from sticking together and forming gel clumps due to excessive water absorption. Let stand for 5 to 8 minutes to allow the SAP resin to fully absorb the water and form a uniformly dispersed suspension of water-containing gel particles.

[0070] Immediately sprinkle the 5% dry powder mixture reserved in step S1 into the semi-wet SAP gel in batches, stirring rapidly while sprinkling, so that the dry powder is evenly coated on the outer surface of the SAP gel particles, forming an artificial mineral shell.

[0071] Step S4: Mixing and stirring to make pulp:

[0072] Add the remaining dry powder mixture and the remaining mixing water from step S2 to the mixer, start the mixer and stir at 100 r / min for 2 minutes to initially wet and mix the dry powder with the water; then pour the humidity-responsive water-retaining microparticles obtained in step S3 evenly into the mixer, increase the mixer speed to 400 r / min and stir for 5 minutes to obtain the final product.

[0073] Comparative Example 1:

[0074] The comparative example material is ordinary ultrafine cement paste, which is based on 1000g of ultrafine cement, with only 550g of mixing water added according to a water-cement ratio of 0.55, without any admixtures, and is prepared by conventional mixing.

[0075] Experimental example:

[0076] Four groups of grouting materials were prepared according to the methods described in Examples 1 to 3 and the comparative examples, and their performance was tested, as follows:

[0077] The fluidity of the slurry was tested using a Marsh funnel; the workable time, i.e., the initial setting time, was tested using a Vicat apparatus equipped with an initial setting needle; the compressive strength was tested by cutting a 40 mm × 40 mm × 160 mm specimen in half; the 28-day expansion rate was measured using the prism length variation method; the minimum groutable crack width was determined using a mortar board with 0.05 mm artificial parallel cracks, and the continuous slurry discharge distance was recorded under a constant pressure of 0.30 MPa; the experimental data are shown in Table 1.

[0078] Table 1: Performance Comparison Table

[0079]

[0080] Comprehensive comparative analysis, comparing Examples 1 to 3 with the comparative examples, shows that:

[0081] (1) Adaptability of operating time: The present invention uses 0.3%~0.8% trace retarder to precisely control the operating time to 68~118 min (comparative example only 38 min), which perfectly matches the time window requirements of long-distance transportation and complex construction conditions in Northwest China.

[0082] (2) High balance between strength and flowability: Although the water-cement ratio of the present invention (0.50~0.60) is comparable to or slightly higher than that of the comparative example (0.55), thanks to the multi-level filling and reinforcement effect of silica fume-nano silica, the 28-day compressive strength (50.7~60.8MPa) is still 32%~58% higher than that of the comparative example (38.5 MPa).

[0083] (3) Significant leap in anti-shrinkage performance: Humidity-responsive water-retaining microparticles and expansion agents control the 28-day shrinkage rate at 0.048%~0.071%, which is 63%~75% lower than the 0.192% of the control ratio. This completely solves the engineering pain point of grouting materials in the arid and windy areas of Northwest China debonding and secondary cracking due to rapid water loss.

[0084] Finally, it should be noted that the above embodiments are merely examples for clearly illustrating the present invention and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.

Claims

1. A method for preparing an ultrafine cement-based composite grouting material, characterized in that, Includes the following steps: Step S1: Prepare raw materials according to the following mass ratio: based on the mass of ultrafine cement, silica fume 6%~12%, silica powder 0.5%~1.5%, retarder 0.3%~0.8%, mixing water with a water-cement ratio of 0.5~0.6, SAP resin 0.2%~0.5%, defoamer 0.1%~0.3%, and expanding agent 7%~10%; Step S2: Mix the ultrafine cement, silica fume, nano silica powder, retarder, expanding agent and defoamer dry powder to obtain a basic dry powder mixture, and take out 5% of the dry powder mixture by mass of the basic dry powder for separate use. Step S3: Take a portion of the mixing water to pre-wet and disperse the SAP resin, add the prepared portion of the basic dry powder mixture for coating treatment, and obtain humidity-responsive water-retaining microparticles. Step S4: Mix the remaining dry powder mixture from step S2 with the remaining mixing water, then add the humidity-responsive water-retaining microparticles obtained in step S3, and continue stirring to obtain the grouting slurry.

2. The preparation method of the ultrafine cement-based composite grouting material as described in claim 1, characterized in that, The specific operation of the pre-wet dispersion in step S3 is as follows: slowly sprinkle the SAP resin into a mixing water that is 5 times its mass, stirring while sprinkling, and let it stand for 5 to 8 minutes to form a suspension of hydrogel microparticles.

3. The preparation method of the ultrafine cement-based composite grouting material as described in claim 1, characterized in that, The specific operation of the coating process in step S3 is as follows: 5% of the total mass of the base dry powder mixture is sprinkled into the suspension of hydrogel microparticles, and stirred until the dry powder is evenly coated on the surface of the SAP gel particles to form an artificial mineral shell.

4. The preparation method of the ultrafine cement-based composite grouting material as described in claim 1, characterized in that, Step S4 specifically involves: adding the remaining dry powder mixture and the remaining mixing water into a mixer and stirring at 100 r / min for 2 minutes, then adding the humidity-responsive water-retaining microparticles and increasing the speed to 400 r / min and stirring for 5 minutes.

5. An ultrafine cement-based composite grouting material, characterized in that, The composite grouting material is prepared by the preparation method described in any one of claims 1 to 4.